2016
DOI: 10.2514/1.t4665
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Dispersal Characteristics of Liquid Breakup in Vacuum

Abstract: This work presents an experimental and numerical study on the dispersal characteristics of a liquid jet ejecting into vacuum. The liquid breaking is mainly caused by flash evaporation and bubbles expansion. Experiments of liquid dispersing under different conditions show that the superheat degree is the most important parameter influencing the pattern of the breaking liquid. The jet velocity has large influence on the distribution of the particle sizes. Mixing some volatile liquid with nonvolatile liquid can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…The second main parameter is the injection pressure PN. Up to a certain value, the rise of the injection pressure results in a decrease of the obtained droplet size [27].…”
Section: Short State Of the Art On Spray Flash Evaporation 321 Litera...mentioning
confidence: 96%
See 1 more Smart Citation
“…The second main parameter is the injection pressure PN. Up to a certain value, the rise of the injection pressure results in a decrease of the obtained droplet size [27].…”
Section: Short State Of the Art On Spray Flash Evaporation 321 Litera...mentioning
confidence: 96%
“…Some authors reported the effect of a third parameter, the discharge or backpressure PV, on the stability of the jet which decreases by reducing the chamber pressure. Most of the reported studies occur at a discharge pressure corresponding to the ambient pressure and very few studies were carried out under vacuum [27,28]. Table 5 sums up the operating conditions for flash evaporation studied in literature.…”
Section: Short State Of the Art On Spray Flash Evaporation 321 Litera...mentioning
confidence: 99%
“…Thus, in analyzing long-term discharge of liquid microjets into vacuum (a strongly rarefied medium), certain differences were revealed in the processes of discharging both from an aperture and long capillary from those described in literature [9,[13][14][15]. First of all, this is an extreme instability of the flow shape that remains relatively stable in measuring for very short time intervals.…”
mentioning
confidence: 89%
“…Later, Vieira and Simões-Moreira [35] proved this physical model by the experimental method and observed the blocking behavior as well as the existence of the evaporation wave. Meanwhile, many scholars [35][36][37] have carried out abundant experiments on jet flash evaporation under low pressure.…”
Section: Film Flash Evaporationmentioning
confidence: 99%
“…The liquid flash evaporation has been used in the America-Russian space station. Hence, many scholars have carried out abundant studies in order to protect the safe stable running of air vehicles [37,68]. In this paper, key attentions were paid to applications of flash evaporation, which was not introduced in detail here.…”
Section: Oil Supplymentioning
confidence: 99%